Novel combination of zero-valent Cu and Ag nanoparticles @ cellulose acetate nanocomposite for the reduction of 4-nitro phenol - Khan, F.U. (Elsevier B.V., 2017)
A very simple and low-cost procedure has been adopted to synthesize efficient copper (Cu), silver (Ag) and copper-silver (Cu-Ag) mixed nanoparticles on the surface of pure cellulose acetate (CA) and cellulose acetate-copper oxide nanocomposite (CA-CuO). All nanoparticles loaded onto CA and CA-CuO presented excellent catalytic ability, but Cu-Ag nanoparticles loaded onto CA-CuO (Cu0-Ag0/CA-CuO) exhibited outstanding catalytic efficiency to convert 4-nitrophenol (4-NP) into 4-aminophenol (4-AP) in the presence of NaBH4. Additionally, the Cu0-Ag0/CA-CuO can be easily recovered by removing the sheet from the reaction media, and can be recycled several times, maintaining high catalytic ability for four cycles. © 2017 Elsevier B.V.